2021
DOI: 10.1177/00222437211010465
|View full text |Cite
|
Sign up to set email alerts
|

How (and When) the Presence of Food Decreases Enjoyment of Customer Experiences

Abstract: Consumers frequently engage in experiences (e.g., listening to music) in the presence of delicious food. Ten studies show that the presence (vs. absence) of such food decreases the enjoyment of a concurrent (target) experience across a wide array of consumption activities, such as listening to music, evaluating pictures, and coloring. The presence (vs. absence) of food prompts mental imagery of consuming that food, which decreases engagement with the target experience, resulting in lower enjoyment. Consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…Immersion refers to feelings of being fully absorbed, engrossed, or engaged in an experience (Garbinsky and Klesse 2021; Higgins and Scholer 2009; Tonietto and Barasch 2021). It is closely related to engagement (Diehl, Zauberman, and Barasch 2016; Woolley and Sharif 2022), although the term “engagement” can also refer to the interaction between a consumer and a firm (such as when consumers share firm-generated videos; Kumar and Pansari 2016; Valsesia, Proserpio, and Nunes 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Immersion refers to feelings of being fully absorbed, engrossed, or engaged in an experience (Garbinsky and Klesse 2021; Higgins and Scholer 2009; Tonietto and Barasch 2021). It is closely related to engagement (Diehl, Zauberman, and Barasch 2016; Woolley and Sharif 2022), although the term “engagement” can also refer to the interaction between a consumer and a firm (such as when consumers share firm-generated videos; Kumar and Pansari 2016; Valsesia, Proserpio, and Nunes 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Conversely, Barnett and Grabe (2000) find that viewing negative videos (e.g., news stories about a house fire) in slow motion triggers more negative feelings. Since immersion intensifies the valence of an experience, making positive experiences more positive and negative experiences more negative (Diehl, Zauberman, and Barasch 2016; Garbinsky and Klesse 2021; Higgins and Scholer 2009), this logic may explain how slow motion intensifies emotional valence—by eliciting immersion.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(2018) suggested that psychological imagination can increase the originality and practicality of products. According to Garbinsky and Klesse (2021), the presence of food stimulates customers' psychological imagination of consuming these foods, which reduces the integration of the target experience and leads to a lower positive experience. DeRosia and Elder (2019) found that managers have some negative effects on the psychological phenomena of end customers, therefore, DeRosia and Elder (2019) proposed an effective analysis technology to avoid the negative effects of psychological imagination.…”
Section: Evolution Of Hotspots In Customer Experience Researchmentioning
confidence: 99%
“…, 2019; Kesgin et al. , 2022), as well as key marketing management objectives (Lemon and Verhoef, 2016; Garbinsky and Klesse, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These types of strategies are essential in today's industry because it has been observed that, in the highly competitive and dynamically changing restaurant sector, managers' proactive behaviour and ability to create a unique experience with a personal signature is becoming crucial. Not in vain, understanding, creating and managing customer experiences and enhancing their consequences have been shown to be key to consumer behaviour (Bastiaansen et al, 2019;Kesgin et al, 2022), as well as key marketing management objectives (Lemon and Verhoef, 2016;Garbinsky and Klesse, 2021).…”
mentioning
confidence: 99%